Endoscopic observation of the palisade vessels in Killian–Jamieson diverticulum was useful for diagnosis and surgical treatment: a case report - Yasunori Kurahashi; Yudai Hojo; Tatsuro Nakamura; Tsutomu Kumamoto; Yasutaka Nakanishi; Yoshinori Ishida; Hisashi Shinohara (Surgical Case Reports)
Abstract Background Killian–Jamieson diverticulum is a rare pharyngoesophageal diverticulum that arises below the cricopharyngeus muscle. Unlike the most common Zenker’s diverticulum, which requires cricopharyngeal and esophageal myotomy, diverticulectomy is sufficient for surgical treatment of Killian–Jamieson diverticulum. Thus, accurate preoperative diagnosis is indispensable for avoiding unnecessarily invasive surgery. Here, we report a case of Killian–Jamieson diverticulum in which endoscopic observation of the palisade vessels was useful for diagnosis and intraoperative endoscopy was effective in guiding surgical resection. Case presentation A 65-year-old woman complained of pharyngeal discomfort and increased coughing and was referred to our hospital with a diagnosis of a pharyngoesophageal diverticulum. Contrast esophagography and cervical computed tomography revealed a diverticulum measuring 3 cm in diameter on the left side of the cervix. The diverticulum was identified by endoscopy just below the palisade vessels, which represents the level of the upper esophageal sphincter, and was diagnosed as Killian–Jamieson diverticulum. She underwent diverticulectomy without cricopharyngeal and esophageal myotomy. After exposing the diverticulum under light from the endoscope and washing out the food residue inside endoscopically, the diverticulum was resected using the endoscope as a bougie so as not to narrow the esophagus. The postoperative course was uneventful, and she remains asymptomatic without recurrence or stenosis at 6 months after surgery. Conclusions Endoscopic observation of the palisade vessels in addition to esophagography can help diagnose Killian–Jamieson diverticulum and determine the optimal surgical procedure. Diverticulectomy can be performed intentionally and safely with the aid of intraoperative endoscopy.